A new frontier for an old drug? A word of caution for beta-blockers in sepsis!. (3rd October 2015) - Maybauer, Marc O.; Maybauer, Dirk M.
Abstract: Recent promising findings indicate a possible benefit of β-blockade in septic patients. Ongoing trials on esmolol in septic shock are investigating its hemodynamic effects, focusing on heart rate control and echocardiographic changes, as well as potential anti-inflammatory effects. However, given the complex physiology of sepsis and pharmacological effects on β-blockade, large multi-center trials are essential before such a therapy may be applied safely.